2021
DOI: 10.1051/0004-6361/202040004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of apsidal motion in eclipsing binaries using TESS data

Abstract: Context. The change in the argument of periastron of eclipsing binaries, that is, the apsidal motion caused by classical and relativistic effects, can be measured from variations in the difference between the time of minimum light of the primary and secondary eclipses. Poor apsidal motion rate determinations and large uncertainties in the classical term have hampered previous attempts to determine the general relativistic term with sufficient precision to test general relativity predictions. Aims. As a product… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 76 publications
2
29
0
Order By: Relevance
“…Combining 35 new, precise apsidal motion rates from Baroch et al (2021) and Claret et al (2021) with 16 additional data points of apsidal motion rates as well as measurements of the RM effect and gravity darkening from the literature, we are able to find consistent results of misalignment for the two binary systems DI Her and CV Vel where misalignment is already established. For AS Cam, we agree on the hypothesis by Pavlovski et al (2011) that the low apsidal motion rate of AS Cam can be explained by spin-orbit misalignment alone.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Combining 35 new, precise apsidal motion rates from Baroch et al (2021) and Claret et al (2021) with 16 additional data points of apsidal motion rates as well as measurements of the RM effect and gravity darkening from the literature, we are able to find consistent results of misalignment for the two binary systems DI Her and CV Vel where misalignment is already established. For AS Cam, we agree on the hypothesis by Pavlovski et al (2011) that the low apsidal motion rate of AS Cam can be explained by spin-orbit misalignment alone.…”
Section: Discussionmentioning
confidence: 59%
“…1 With these assumptions we then attribute any discrepancy between the observed and expected apsidal motion rate to a misalignment of stellar spin axes, or if agreement is found, determine upper limits on any potential obliquity. The recent high-precision apsidal motion determinations by Baroch et al (2021) and Claret et al (2021) using TESS light curves sparked this idea and their data compose the bulk the apsidal motion rates that we use.…”
Section: Our Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…TESS can also contribute to period analysis for EBs with apsidal motion. Baroch et al [271] used TESS data to study apsidal motion in 15 EBs and determine the apsidal periods of nine of these. A comparison of these with theoretical models by Claret et al [272] found good agreement.…”
Section: Standard Ebsmentioning
confidence: 99%